2011
DOI: 10.1007/s10194-011-0399-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of migraine in the age of genome-wide association studies

Abstract: Genetic factors importantly contribute to migraine. However, unlike for rare monogenic forms of migraine, approaches to identify genes for common forms of migraine have been of limited success. Candidate gene association studies were often negative and positive results were often not replicated or replication failed. Further, the significance of positive results from linkage studies remains unclear owing to the inability to pinpoint the genes under the peaks that may be involved in migraine. Problems hampering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 67 publications
0
77
1
1
Order By: Relevance
“…On the other hand, several genetic polymorphisms probably increase thrombotic disorders among the migraineurs; however, these putative genes are extremely different from those linked to IBS. For examples, migraine related candidate genes include factor V Leiden , factor V ( H1299R ), prothrombin ( G20210A ), factor XIII ( V34L ), β-fibrinoge n and lipoprotein receptor ( LRP1 ) etc, whereas IBS related candidate genes consist of serotonin transporter ( SLC6A4 ), norepinephrine transporter ( NET ), alpha-2A-adrenergic receptors ( ADRA2A ), interleukin-10 ( IL-10 ), G protein β3 subunit ( GNβ3 ) and sodium channel ( SCN5A ) etc 73,75,76. In fact, the potential functions of these genetic variants are controversial because they result in a small to moderate risk of developing migraine which means that migraine is a heterogeneous disorder.…”
Section: Pathogenesesmentioning
confidence: 99%
“…On the other hand, several genetic polymorphisms probably increase thrombotic disorders among the migraineurs; however, these putative genes are extremely different from those linked to IBS. For examples, migraine related candidate genes include factor V Leiden , factor V ( H1299R ), prothrombin ( G20210A ), factor XIII ( V34L ), β-fibrinoge n and lipoprotein receptor ( LRP1 ) etc, whereas IBS related candidate genes consist of serotonin transporter ( SLC6A4 ), norepinephrine transporter ( NET ), alpha-2A-adrenergic receptors ( ADRA2A ), interleukin-10 ( IL-10 ), G protein β3 subunit ( GNβ3 ) and sodium channel ( SCN5A ) etc 73,75,76. In fact, the potential functions of these genetic variants are controversial because they result in a small to moderate risk of developing migraine which means that migraine is a heterogeneous disorder.…”
Section: Pathogenesesmentioning
confidence: 99%
“…A number of large GWAS aiming to identify associations between genetic variants and migraine have been conducted, with the first being published by the International Headache Genetics Consortium (IHGC) in 2010 (Anttila et al, 2010;Schurks, 2012). Two subsequent GWAS conducted by the Dutch-Icelandic migraine genetics consortium (DICE) and the Women's Genome Health Study (WGHS) failed to replicate the results from the first GWAS and only identified modest associations (Ligthart et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…If one parent has migraine, there is a 50% chance of the offspring developing migraine. 51 Should both parents have migraine, the risk of migraine is 80%. The suspicion of a migraine diagnosis should be high when multiple family members have disabling episodic headaches.…”
Section: The Inheritance Of Migrainementioning
confidence: 99%